Creating a Video Using Canva Application as an English Learning Media of Recount Text Material - Sheila Melinia; Nugroho Nugroho (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Currently, educational videos have become an essential part of higher education. It is related to the use of learning media, which has an essential role in education, and the use of technology in education which is good to support teachers in transferring knowledge to students to improve their skills or knowledge. Students and teachers have used the implementation of media in the classroom. One media commonly used in the learning process is the animation video, such as the Benin animation video and especially the Canva application as the basis for making learning materials. The implementation of animation videos in the classroom brings several perceptions toward students. Therefore, this article aims to describe how to use the Canva application to create a video as learning recount text material designed by searching for relevant literature sources. This1research shows that the Canva application is1helpful1and easy for teachers to create educational videos.